The Entrepreneurial Investor: The Art, Science, and Business of Value Investing - Orfalea Paul (John Wiley, 2007)
The Entrepreneurial Investor will inspire you to treat investing like a business and to think of yourself as an owner. Through solid examples and a light narrative, Paul Orfalea skillfully explores the essence of the entrepreneurial investor, which includes balancing the art and science of this discipline, and viewing investing itself as a business. Along the way, he also examines how the elements of focus, opportunism, and involvement can improve your overall investment results.